Art and power: contemporary figurations - Conde, Idalina (2012)
In this text the issue of art and power is approached from a perspective that addresses, in particular, the symbolical – essential – power of artists through their ideas as authors. A double perspective that relates not only to the creative figuration of those ideas, illustrated here by some of the art works presented at the last Documenta in Kassel (2007), one of the pinnacles of contemporary art, but also to the chessboard of powers in artistic spaces. A figuration of interdependencies that raises questions about artistic power and its sovereignty and fragilities in the contemporary situation. In the light of the various forms of hetero-determination and hetero-legitimation of art that today subordinate this kind of reflection to the role of its patronage, intermediation, markets, media coverage and reception, among other instrumental uses of art and culture, the text then attempts to (re)position the power of artists in what seems to be a space that has been colonised by other powers.